SAPTA PESONA OBJEK WISATA PANTAI PURUS MUARO LASAK KECAMATAN PADANG BARAT KELURAHAN RIMBO KALUANG PADANG - Maulina, Sri Silvia (STKIP PGRI Sumbar, 2014)
This study aimed to obtain information about public participation in the attraction Purus Beach restless District of Muara Padang Padang Kaluang Rimbo West Village.This research is qualitative. Engineering researchers is the determination of the informant by purposive sampling is business Attractions, Community. Data was collected through interviews and documentation.The results of the field study of how peoples participation in coastal objekwisata purus restless District of Muara Padang Padang West Village Rimbo Kaluang as follows: 1) kebersaihan at Purus Beach Muaro attraction restless still less clean because the lack of public participation in the cleanliness of tourist objects. In keeping proposed by (Bakaruddin 2009: 84) net is a state or condition of environment featuring an atmosphere free of dirt, rubbish, waste, disease and pollution. 2) in terms of good security because of the cooperation of local communities. Security is when tourists would love to visit someplace where feel safe, comfortable, peaceful, no fear, and ter protected from evil. 3) souvenirs on attraction Purus Beach Muaro Application energetic yet so visitors who come not to bring souvenirs home gained in attraction. 4) Welcoming at Purus Beach attraction has good energetic Muaro it all visible from any public officer or around attractions serve visitors need assistance or information. 5) The Attraction Coolness antai Purus Muaro restless already in tumbuhi trees so add coolness and comfort in the attraction. 6) The beauty of the situation or atmosphere featuring an attractive environment and unsightly. 7) Conditions orderly is something highly coveted by everyone, including wisatawa. Reflecting on a regular atmosphere, neat and smooth and showed a lot of discipline in all aspects of community life.